The application of nanomaterials for the delivery of natural antimicrobials in engineered systems - Chan, A (2013)
Biofouling is the undesired biofilm formation on surfaces at a liquid interface that interferes with the affected substrate’s function. It is a ubiquitous problem in many engineered systems in industry. Biofouling causes contamination, essential damage to materials, and impedances to crucial industrial processes. These adverse effects lead to health hazards, gross increase in energy consumption, and significant decrease in overall productivity, all of which result in higher operational costs and environmentally destructive consequences. Interest in discovering effective alternatives to conventional antimicrobial agents has gained momentum. Current anti-biofouling strategies have significant disadvantages, such as the generation of toxic by-products, indiscriminate corrosion of surrounding materials and the environment, and promotion of resistance development. Alternative methods of controlling biofouling are in high demand because present-day solutions are far from sustainable. Plant secondary metabolites are promising candidates as novel biocides because they are (i) highly effective in killing microbes while being non-toxic to humans at antimicrobially active concentrations, and (ii) safer and non-damaging to the natural environment. Herein, antimicrobial efficacies of five plant-derived compounds were assessed against various species of planktonic bacteria as well as biofilms at various maturity stages. Allyl isothiocyanate (AIT) and cinnamaldehyde (CNAD) displayed the greatest inhibitory effects against all planktonic species tested. The minimum inhibitory concentration is defined as the lowest concentration of a substance that inhibits visible microbial growth, and the MBC is defined as the lowest concentration at which 99.9% of the population is killed. AIT yielded MICs of 156.25 mg/L and MBCs of 156.25 to 312.5 mg/L, and CNAD yielded MICs of 78.125 to 156.25 mg/L and MBCs of 78.125 to 312.5 mg/L. Furthermore, 312.5 mg/L AIT and 625 mg/L CNAD successfully reduced > 80% of biofilm adhesion as compared to negative controls. AIT and CNAD were therefore further evaluated extensively. Hindered by their volatile nature and immiscibility, plant secondary metabolites typically do not reach their maximum antimicrobial capacity due to low bioavailability. Thus, they would benefit from being protected and delivered in nano-sized carriers. In this study, mesoporous silica nanoparticles (MSNs) were evaluated as carriers for AIT and CNAD delivery. In one, employment of MSNs as carriers doubled the antibacterial efficacy of free form AIT and increased kill rate of free form CNAD by six times. Furthermore, free form AIT caused ~70% of 60 day-old biofilm to detach, whereas AIT-loaded MSNs essentially removed all of the biofilm. As for CNAD, its free form had no significant effect, whereas CNAD-loaded MSNs caused ~80% reduction in biofilm biomass. MSNs were further engineered to incorporate lactose pore caps to achieve specific, on-command delivery. These MSNs were designed to respond to external stimuli intelligently, with gatekeepers that degrade only in the vicinity of certain target bacteria that are able to metabolise lactose. Capped AIT-loaded MSNs reduced bacterial viability by ~85% as compared to the negative control, while capped CNAD-loaded versions reduced viability by ~40%. This stimuli-triggered MSN delivery technology would be more sustainable than current methods because resistance development would be lowered, and the delivery vehicles could be recycled and reused. Herein, the complete AIT- or CNAD-loaded, lactose-capped MSNs delivery complex proved to be an effective and environmentally conscientious system for killing unwanted bacteria.